Rekonstruksi Simbolisme Laut dalam Alkitab: Hermeneutik Ekologis-Kontekstual Masyarakat Pesisir Maluku - Margaretha Martha Anace Apituley (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. The sea in the Bible is often used as a symbol of chaos and destructive power, influenced by ancient Southwest Asian cosmology and continental-oriented hermeneutics. This approach often ignores the ecological and spiritual dimensions in the experiences of coastal communities, particularly in Moluccas, who interpret the sea as a space of life and a sacred relationship with creation. This article aims to reconstruct the symbolism of the sea through ecological-contextual hermeneutics using intertextual analysis of key texts: Job 7:12, Isaiah 57:20, Mark 4:37–41, Revelation 13:1 & 21:1, and ethnographic data from eight coastal communities. The result shows that the sea reflects restoration, divine presence, and ecosystem vitality, opening space for the development of ecological spirituality and church involvement in preserving the sea as an integral part of God's creation.Abstrak. Laut dalam Alkitab sering digunakan sebagai lambang kekacauan dan kekuatan destruktif, yang mana hal tersebut dipengaruhi oleh kosmologi Asia Barat Daya kuno dan hermeneutik continental oriented. Pendekatan ini sering mengabaikan dimensi ekologis dan spiritual dalam pengalaman masyarakat pesisir, khususnya di Maluku, yang memaknai laut sebagai ruang kehidupan dan relasi sakral dengan ciptaan. Artikel ini bermaksud untuk merekonstruksi simbolisme laut melalui hermeneutik ekologis-kontekstual dengan menggunakan analisis intertekstual teks kunci: Ayub 7:12, Yesaya 57:20, Markus 4:37–41, Wahyu 13:1 & 21:1, dan data etnografis delapan komunitas pesisir. Hasil penelitian menunjukkan laut mencerminkan pemulihan, kehadiran ilahi, dan vitalitas ekosistem, membuka ruang bagi pengembangan spiritualitas ekologis serta keterlibatan gereja dalam pelestarian laut sebagai bagian integral ciptaan Allah.